Cation Vacancy in Wide Bandgap III‐Nitrides as Single‐Photon Emitter: A First‐Principles Investigation. Issue 18 (26th July 2021) - Zang, Hang; Sun, Xiaojuan; Jiang, Ke; Chen, Yang; Zhang, Shanli; Ben, Jianwei; Jia, Yuping; Wu, Tong; Shi, Zhiming; Li, Dabing
Abstract: Single‐photon sources based on solid‐state material are desirable in quantum technologies. However, suitable platforms for single‐photon emission are currently limited. Herein, a theoretical approach to design a single‐photon emitter based on defects in solid‐state material is proposed. Through group theory analysis and hybrid density functional theory calculation, the charge‐neutral cation vacancy in III‐V compounds is found to satisfy a unique 5‐electron‐8‐orbital electronic configuration with T d symmetry, which is possible for single‐photon emission. Furthermore, it is confirmed that this type of single‐photon emitter only exists in wide bandgap III‐nitrides among all the III‐V compounds. The corresponding photon energy in GaN, AlN, and AlGaN lies within the optimal range for transfer in optical fiber, thereby render the charge‐neutral cation vacancy in wide‐bandgap III‐nitrides as a promising single‐photon emitter for quantum information applications. Abstract : Neutral cation vacancy in wide bandgap III‐nitrides including AlN, GaN, and AlGaN is predicted to be suitable for single‐photon emission, it has zero phonon line that lies within the optimal range for transmission in optical fiber and a moderate radiative rate, thereby render it as a promising single‐photon emitter for quantum information applications.